Contrast-Enhanced Digital Mammography (CEDM) (Springer International Publishing, 2018)
This book offers a comprehensive, practical resource entirely devoted to Contrast-Enhanced Digital Mammography (CEDM), a state-of-the-art technique that has emerged as a valuable addition to conventional imaging modalities in the detection of primary and recurrent breast cancer, and as an important preoperative staging tool for women with breast cancer. CEDM is a relatively new breast imaging technique based on dual energy acquisition, combining mammography with iodine-based contrast agents to display contrast uptake in breast lesions. It improves the sensitivity and specificity of breast cancer detection by providing higher foci to breast-gland contrast and better lesion delineation than digital mammography. Preliminary results suggest that CEDM is comparable to breast MRI for evaluating the extent and size of lesions and detecting multifocal lesions, and thus has the potential to become a readily available, fast and cost-effective examination. With a focus on the basic imaging principles of CEDM, this book takes a practical approach to breast imaging. Drawing on the editors' and authors' practical experience, it guides the reader through the basics of CEDM, making it especially accessible for beginners. By presenting the key aspects of CEDM in a straightforward manner and supported by clear images, the book represents a valuable guide for all practicing radiologists, in particular those who perform breast imaging and have recently incorporated or plan to incorporate CEDM into their diagnostic arsenal.